Contributions to the Pleistocene geology of the Nile Valley - Butzer, Karl W. (ERDKUNDE, 1959)
The Pleistocene terraces of the Nile valley, whose study was initiated by K. S. SANDFORD in a fundamental work of many years 1926-1933, were newly investigated by the author in 1958 for the purpose of a distinction of local climatic (in Egypt as well as south of the Sahara) and eustatically caused graveling. First, a Quaternary geological mapping was carried out in Middle Egypt. Thereby it turned out: 1) Nile deposits in recognizable morphological levels are completely missing between Beni Adi and Mallawi. 2) North of Mallawi, levels can be traced at 78 and 90-98 m above river level (sicily) to the sea ¡south of Mallawi, these are absent for 300 km to Gebelein, where similar levels, but probably not contemporaneous, can be recognized. There is no 46-m terrace level north of Gebelein. 3) A 25-30-m terrace is common throughout Egypt, except for the 140-km Beni Adi-Beni Mazar section. North of this is a eustatic terrace with Acheul (Tyrrhenia), south is an older pluvial terrace with Abbeville. 4) A 10-15 m terrace is also interpluvial and eustatic in Lower Egypt (Monastiria), climatic in Upper Egypt (with Acheul). This distinction was made on the basis of terrace composition, soil formations and known industries. On the basis of soil profiles the following sequence took place several times: a) sand deposition by Nile and Wadis. b) final accumulation of gravels (in Upper Egypt), c) brown earth formation with mighty lime enrichment horizons, d) local aridity with suspension of chemical weathering as well as soil formation. Simultaneous eustatic-induced graveling in Lower Egypt, c) red earth formation with decalcification. The wadi profiles of Upper Egypt also indicate a complicated valley development during the Late Pleistocene (3-4 and 1-2 m wadi terraces).